Budidaya Indigofera di Lahan Pasca Tambang Timah - Yuliana, Yuliana; Wulandari, Feby; Amalliah, Mifta; Lestari, Tri (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2024)
Yuliana, Y., Wulandari, F., Amalliah, M., Lestari, T. (2024). Indigofera cultivation in post-tin mining land. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 600–608). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The optimal availability of land for the development of forage in Indonesia is increasingly narrow. Suboptimal land in Bangka Belitung continues to increase due to tin mining activities. Indigofera as an alternative plant is cultivated on post-tin mining land for livestock use. The aimed of this research is to determine the growth and cultivation techniques of Indigofera on post-tin mining land. The research was carried out from July to September 2024. The research location was at the Kampoeng Water Reclamation land at Jangjang, Dwi Makmur Village, Merawang District, Bangka Regency. The method used in this research activity is a single randomized group design (RAK) experimental method. Randomized block design with several ameliorant treatments. The treatments used were A0 control (without treatment), A1 with the addition of cow manure, A2 with the addition of cassava peel waste and cow manure, A3 with the addition of cassava peel waste which had been turned into block compost. The results of the research showed that the growth response of indigofera was significantly different to the administration of several ameliorants. Providing cow manure provides better plant growth compared to other treatments. The application of cow manure showed the best treatment for the parameters of plant height, number of leaves and number of stalks on indidigofera plants. Indigofera plants are recommended as animal feed on post-tin mining land.